Education for entrepreneurship: In search of the fifth pillar Learning to be entrepreneurial - Cruzata-Martínez, Alejandro (2021)
Currently, the entrepreneurship boom is on the rise, education centers from elementary to higher education are betting on providing an entrepreneurial education. The purpose of this article is: To recognize the development of social entrepreneurship competencies from the four pillars of education, adding a fifth pillar which “knows how to be an entrepreneur". In addition, it is achieved: to recognize the transforming mission of social entrepreneurship competencies within the educational field, to identify the challenges faced by educational systems and how school entrepreneurship is adapted, to compare successful experiences of different countries in entrepreneurship, to analyze the importance of entrepreneurial education from the four pillars as a basis for the construction of the fifth pillar "Learning to undertake" and to differentiate the roles of the educational community. Consequently, documentary analysis is used, after selecting articles, various books, congresses, etc. related to educational entrepreneurship.